SMART OSIS: PEMANFAATAN MICROSOFT EXCEL UNTUK EFISIENSI ORGANISASI - Alfian Febiyanto; Arief Alkhoir; Irwanto Sitorus; Kristian Pati Wator; Mula Arman Gulo; Muhamad Fauzan Zibran; Perianto; Sri Ayu Maryati; Yusuf Ilham Zamzami; Zakaria; Dede Handayani (Abdi Jurnal Publikasi, 2025)
The advancement of technology demands that the younger generation possess strong digital skills, including in managing school organizations. This Community Service Activity (PkM) aims to enhance digital literacy and improve the operational efficiency of the Intra-School Student Organization (OSIS) through Microsoft Excel training at SMP Negeri 3 Teluknaga. This activity is an implementation of the Tri Dharma of Higher Education by students of the Informatics Engineering Study Program at Universitas Pamulang. The methods used include lectures, demonstrations, and hands-on practice, focusing on financial management, schedule planning, and OSIS membership administration. The results of the activity showed a significant improvement in students' understanding and skills in using Excel for organizational needs. In addition to providing practical benefits, the training also lays the foundation for a smarter, more transparent, and data-driven organization. This activity is expected to be a starting point in realizing a